How Does Talk Around Reading Influence Comprehension in Third Grade? - Karen Gruhn Tomczak (Networks: An Online Journal for Teacher Research, 2014)
This study attempts to document the efficacy of peer-support and self-monitoring during partnered reading by third grade students as evidenced by their discourse. Pairs of third grade students engaged in partnered reading in a general education third grade classroom. Their oral reading, coaching and conversations were recorded using i-Pod2s over the course of twenty days. The digital audio recordings were then analyzed to determine if the students employed reading strategies, what types of reading strategies they used, and how other discourse between the students influenced reading behaviors.